2007
DOI: 10.7547/0970460
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Study of the Size of the First Metatarso-Digital Segment in Feet with Incipient Hallux Limitus

Abstract: The size of the first metatarso-digital segment could be implicated in the development of hallux limitus deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Other muscles of the lower limb, whose muscles’ MTrPs could be activated are the vastus lateralis, tensor fasciae latae, gemellus superior and inferior, soleus, tibialis anterior and the peroneus brevis [ 2 ],[ 28 ]. However, an excessively index plus foot has been associated with hallux rigidus [ 26 ], hallux limitus [ 30 ] and hallux valgus [ 4 ],[ 7 ],[ 9 ],[ 20 ],[ 23 ],[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other muscles of the lower limb, whose muscles’ MTrPs could be activated are the vastus lateralis, tensor fasciae latae, gemellus superior and inferior, soleus, tibialis anterior and the peroneus brevis [ 2 ],[ 28 ]. However, an excessively index plus foot has been associated with hallux rigidus [ 26 ], hallux limitus [ 30 ] and hallux valgus [ 4 ],[ 7 ],[ 9 ],[ 20 ],[ 23 ],[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other muscles of the lower limb, whose muscles' MTrPs could be activated are the vastus lateralis, tensor fasciae latae, gemellus superior and inferior, soleus, tibialis anterior and the peroneus brevis [2,28]. However, an excessively index plus foot has been associated with hallux rigidus [26], hallux limitus [30] and hallux valgus [4,7,9,20,23,31]. This study needs to be considered in light of three limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, measurement of the longitudinal axis of the first metatarsal bone and the proximal phalanx are used to determinate the HAV angle [15,17,2730]. Tanaka et al [17] reported that, on average, the great toe and first metatarsal of 64 female patients who had hallux valgus were longer than those of normal subjects.…”
Section: Introductionmentioning
confidence: 99%